2008
DOI: 10.1002/gcc.20553
|View full text |Cite
|
Sign up to set email alerts
|

Wilms tumor genetics: Mutations in WT1, WTX, and CTNNB1 account for only about one‐third of tumors

Abstract: Wilms tumor is genetically heterogeneous, and until recently only one Wilms tumor gene was known, WT1 at 11p13. However, WT1 is altered in only ~20% of Wilms tumors. Recently a novel gene, WTX at Xq11.1, was reported to be mutated in Wilms tumors. No overlap between tumors with mutations in WTX and WT1 was noted, suggesting that WT1 and WTX mutations could account for the genetic basis of roughly half of Wilms tumors. To assess the frequency of WTX mutations and their relationship to WT1 mutations in a larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
152
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(166 citation statements)
references
References 19 publications
(25 reference statements)
10
152
2
2
Order By: Relevance
“…However, the majority of the CTNNB1 mutations in tumours with WTX alterations were found in exon 7 or 8, which unlike exon 3 mutations, do not affect the b-catenin serine threonine phosporylation-binding site and therefore may not lead to constitutive b-catenin activation. Mutations in CTNNB1 and WTX were therefore proposed to be not functionally redundant (Ruteshouser et al, 2008), supporting the notion that b-catenin and WTX act in a common pathway. Alternatively, WTX has been independently reported as an APC-interacting protein controlling the subcellular distribution of APC between the cell membrane and the microtubule of epithelial cells (Grohmann et al, 2007), suggesting another tumour suppressor function of WTX independent of WNT signalling.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, the majority of the CTNNB1 mutations in tumours with WTX alterations were found in exon 7 or 8, which unlike exon 3 mutations, do not affect the b-catenin serine threonine phosporylation-binding site and therefore may not lead to constitutive b-catenin activation. Mutations in CTNNB1 and WTX were therefore proposed to be not functionally redundant (Ruteshouser et al, 2008), supporting the notion that b-catenin and WTX act in a common pathway. Alternatively, WTX has been independently reported as an APC-interacting protein controlling the subcellular distribution of APC between the cell membrane and the microtubule of epithelial cells (Grohmann et al, 2007), suggesting another tumour suppressor function of WTX independent of WNT signalling.…”
Section: Introductionmentioning
confidence: 72%
“…WTX (also called AMER1) has been reported to be deleted or mutated in 7-29% of WTs (Rivera et al, 2007;Perotti et al, 2008;Ruteshouser et al, 2008). WTX appears to act as an unusual tumour suppressor gene, in which it is inactivated by one-hit mutational events: mutations in the single X chromosome in tumours from males and the active X chromosome in tumours from females cause inactivation of this gene (Rivera et al, 2007;Perotti et al, 2008;Ruteshouser et al, 2008). Recently, WTX was found to form a complex with AXIN, APC (adenomatous polyposis coli) and b-catenin in the cytoplasm (Grohmann et al, 2007;Major et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WTX mutations exist in tumors with and without b-catenin mutations (Ruteshouser et al, 2008), whereas b-cartenin mutations are found almost exclusively in the presence of loss-of-function mutations of WT1 (Maiti et al, 2000). We previously showed that WT1 inhibited the transcriptional function of both wild-type and constitutively active, gain of function b-catenin alleles .…”
Section: Discussionmentioning
confidence: 99%
“…Without a homologue on the Y chromosome and subjected to X inactivation, WTX is a single copy tumor suppressor; hence loss or mutation of a single allele appears to be sufficient to allow tumor formation. Analysis of a small panel of Wilms tumors initially suggests that WT1 and WTX mutations are mutually exclusive, while later studies with a larger sets of tumors shows that WTX mutations (7-18% of cases) occurs at a similar frequency as WT1 mutations and WT1 and WTX mutations can be found in the same tumor (Perotti et al, 2008;Ruteshouser et al, 2008;Wegert et al, 2009). WTX mutations are rare in other tumor types (Chung et al, 2008;Owen et al, 2008;Yoo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%